Long-term decrease in VLA-4 expression and functional impairment of dendritic cells during natalizumab therapy in patients with multiple sclerosis. - Clara de Andrés (Public Library of Science (PLoS), 2012)
Myeloid and plasmacytoid dendritic cells (mDCs, pDCs) are central to the initiation and the regulation of immune processes in multiple sclerosis (MS). Natalizumab (NTZ) is a humanized monoclonal antibody approved for the treatment of MS that acts by blocking expression of VLA-4 integrins on the surface of leukocytes. We determined the proportions of circulating DC subsets and analyzed expression of VLA-4 expression in 6 relapsing-remitting MS patients treated with NTZ for 1 year. VLA-4 expression levels on pDCs and mDCs decreased significantly during follow-up. In vitro coculture of peripheral blood mononuclear cells and pDCs, with different doses of NTZ in healthy controls (HC) and MS patients showed dose-dependent down-regulation of VLA-4 expression levels in both MS patients and HC, and reduced functional ability to stimulate antigen-specific T-lymphocyte responses. The biological impact of NTZ may in part be attributable to inhibition of transmigration of circulating DCs into the central nervous system, but also to functional impairment of interactions between T cells and DC.